Dynamic mechanical properties of carbon fiber reinforced geopolymer concrete at different ages. Issue 1 (1st January 2023) - Wang, Zhihang; Bai, Erlei; Huang, He; Liu, Chaojia; Wang, Tengjiao
Abstract: In order to improve the strength and toughness of geopolymer concrete (GC) at different ages under impact load, using slag and fly ash as cementitious materials, NaOH and sodium silicate as alkaline activators, carbon fiber as reinforcement, carbon fiber reinforced geopolymer concrete (CFRGC) was prepared. The dynamic compression test of CFRGC was carried out by Φ 100 mm SHPB test system. The effects of age (3 d, 7 d, 28 d) and fiber content on the dynamic mechanical properties of CFRGC were studied, and the strengthening and toughening effects of carbon fiber on GC were analyzed. In addition, the strengthening and toughening effects of carbon fiber on GC and ordinary Portland cement based concrete (PC) were compared and analyzed. The results show that the performance indicators of CFRGC at different ages have strain rate effect under impact load, and the dynamic compressive strength and specific energy absorption of CFRGC increase approximately linearly with the strain rate. With the increase of age, the dynamic compressive strength and specific energy absorption of CFRGC increase, and the strain rate sensitivity of dynamic compressive strength and specific energy absorption also increases. With the increase of carbon fiber content, the dynamic compressive strength and specific energy absorption of CFRGC increase first and then decrease, and the strain rate sensitivity of dynamic compressive strength and specific energy absorption also increase first and then decrease. When the carbon fiber content is 0.2%, the dynamic mechanical properties of CFRGC are the best, and the strain rate sensitivity of performance indicators is the strongest. Carbon fiber has strengthening and toughening effects on GC and PC. When the fiber content is 0.2%, carbon fiber has the best strengthening and toughening effects on GC and PC. The strengthening and toughening effects of carbon fiber on GC is better than that of PC. Compared with 28 d, carbon fiber has better strengthening and toughening effects on GC at the ages of 3 d and 7 d.